Darcy flow and heat transfer of nanoliquid within a porous annulus with incorporating magnetic terms. (January 2023) - Zhang, Ying-Fang; Abu-Hamdeh, Nidal H.; Talabany, Ziyad Jamil; Ajour, Mohammed N.; Hatamleh, Randa I.; Musa, Awad
Abstract: Current investigation was carried out to analyze the treatment of nanomaterial within a domain which experienced magnetic force. Outer rhombus wall is cold and the inner circle has uniform heat flux and due to these conditions, carrier fluid rotates counterclockwise. Darcy law was used for simulation and Joule heating was neglected in equations. Influences of parameters were discussed in plots and contours and CVFEM has been employed to reach such outputs. Rotational core becomes stronger with the rise of Ra while opposite results have been accomplished with the soar of Ha. In cases with higher values of shape factor, Nu has higher values and a similar trend is reported for Rd. Moreover, Nu experiences 30% reduction when Ha augments. This negative impact becomes more sensible when radiation terms are added in equations. Inclusion of nano powders has a favorable impact on Nu although it has a negative impact on temperature gradient.